Interstitial Gas Effect on Vibrated Granular Columns - Melo-Hurtado, F (American Physical Society, 2014)
Vibrated granular materials have been intensively used to investigate particle segregation, convection, and heaping. We report on the behavior of a column of heavy grains bouncing on an oscillating solid surface. Measurements indicate that, for weak effects of the interstitial gas, the temporal variations of the pressure at the base of the column are satisfactorily described by considering that the column, despite the observed dilation, behaves like a porous solid. In addition, direct observation of the column dynamics shows that the grains of the upper and lower surfaces are in free fall in the gravitational field and that the dilation is due to a small delay between their takeoff times. © 2014 American Physical Society.